Pengaruh budaya organisasi dan komitmen organisasi terhadap kinerja karyawan di Universitas Slamet Riyadi (UNISRI) Surakarta - Suripto, Fabiani Rengganesti; Ahsani, Riska Fii (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of organizational culture and organizational commitment on the performance of Universitas ‘Aisyiyah employees with motivation as an intervening variable. This research is quantitative research using a questionnaire as a data collection tool. The sample of this study was 50 employees of the Universitas Slamet Riyadi (UNISRI) Surakarta using a saturated sampling technique and ata analysis using multiple linear regression. The results of this study indicate that there is a positive influence from organizational culture on employee performance with a significance value of 0.001; there is a positive effect of organizational commitment on employee performance with a significance value of 0.005; there is a positive influence of organizational culture and organizational commitment on employee performance with a significance value of 0.000.